The Relationship Between Sexually Transmitted Infections (STIs) and Preterm Birth at Tomalou Primary Health Care Center - Aisyah Fatma Elhartin; Sulistiyah Sulistiyah (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2025)
Preterm birth remains a significant public health concern due to its contribution to neonatal morbidity and mortality worldwide. Among the various risk factors, maternal infections—particularly sexually transmitted infections (STIs)—have been identified as preventable yet critical determinants of premature delivery. This study aimed to examine the relationship between STIs and preterm birth among mothers receiving care at Tomalou Primary Health Care Center. A cross-sectional analytical design was employed, involving 30 postpartum mothers whose medical records and antenatal care data were available. Data on STI status and birth outcomes were collected from health center records and laboratory results, while maternal demographic and obstetric characteristics were also documented. Results indicated that 40% of participants were diagnosed with STIs during pregnancy, and 33.3% experienced preterm birth. Chi-square analysis revealed a significant association between maternal STI status and preterm delivery (p = 0.003). Logistic regression demonstrated that mothers with STIs were sixteen times more likely to deliver prematurely compared to uninfected mothers (OR = 16.0; 95% CI: 2.45–104.3; p = 0.002). These findings suggest that STIs represent a substantial risk factor for preterm birth, even among mothers with adequate antenatal care attendance. Early detection, timely treatment, and comprehensive reproductive health education are recommended to reduce infection-related adverse outcomes. Strengthening STI screening and management within primary healthcare settings is essential to improve maternal and neonatal health outcomes. This study provides evidence for the importance of integrating infection prevention strategies into routine antenatal care to mitigate the risk of premature delivery.